STRATEGI PENINGKATAN KEPUASAN KERJA KARYAWAN PADA PT. METROLOGI GLOBAL SOLUSI (MGS KALIBRASI) KABUPATEN TANGERANG DENGAN MEMPERTIMBANGKAN ASPEK LINGKUNGAN KERJA MELALUI ANALISIS SWOT - Urfa Kamilah Rozi; I Made Aryata (Jurnal Menara, 2025)
This study aims to formulate strategies to improve employee job satisfaction at PT. Metrologi Global Solusi (MGS Kalibrasi), Kabupaten Tangerang, by considering the work environment through a SWOT analysis approach. The research employed a descriptive qualitative method using data collection techniques such as observations, interviews, paper-based questionnaires, and documentation. Work environment indicators include facilities, noise, air circulation, and work relationships, while job satisfaction indicators cover work itself, wages, promotion, supervision, and coworkers. The analysis results indicate that the company is positioned in quadrant I of the SWOT matrix, reflecting a growth-oriented strategy where internal strengths can be optimized to respond to external opportunities. The strategies formulated in order of priority are: offering subscription-based calibration services, regular equipment updates, development of a technology-based work system, certified technician training, strengthening customer service and after-sales support, gradual investment in new equipment, adding digital features to calibration services, expanding cooperation with educational institutions and new industries, and enhancing digital marketing through social media. These strategies are expected to improve employee job satisfaction in various aspects, including work efficiency, career development opportunities, harmonious coworker relationships, and a modern work system that supports productivity.